OCT image atlas of healthy skin on sun‐exposed areas. Issue 4 (25th March 2018) - O'Leary, S.; Fotouhi, A.; Turk, D.; Sriranga, P.; Rajabi‐Estarabadi, A.; Nouri, K.; Daveluy, S.; Mehregan, D.; Nasiriavanaki, M.
Abstract: Background: Skin cancer represents the most prevalent type of cancer in the United States. Excision of these lesions can leave significant scarring, and a delay in the diagnosis of malignant melanoma could result in metastasis or death. Therefore, developing technology and criteria to accurately diagnose these cancers is of particular importance to the medical community. While biopsy can lead to scarring and infections, dermoscopy and confocal microscopy offer noninvasive imaging methods but are also limited in their ability to determine tumor depth and margins. Optical coherence tomography (OCT) is a promising imaging method that uses near‐infrared light backscattering to image structures underneath the surface of the skin. The purpose of this study is to provide examples of variations across different skin locations and to identify common themes that occur with aging and sun exposure, most notably thinning of the epidermis and loss of a distinct dermal‐epidermal junction. Methods: Optical coherence tomography images were taken using the VivoSight swept‐source OCT. Images were taken from a 23‐year‐old man (Subject 1) and an 89‐year‐old man (Subject 2), both with Fitzpatrick Skin Type I, who did not have any prior skin conditions. We investigated the regions of the body that represent sun‐exposed areas. Results: Results including OCT images taken from 19 predominately sun‐exposed areas are shown in Figure 2‐Figure 20. Conclusion: The 2 sets of images demonstrate the variety that exists within OCT imaging of healthy skin, and thus, a comprehensive understanding of the variation in normal skin imaging using OCT is critical to be able to distinguish and diagnose skin cancers when present.